Cultural Acculturation on the Mosque Architecture of the Yoni Al-Mubarok Nganjuk - Latif Kusairi; Depy Tri Budi Siswanto (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
This study aimed to know the culture acculturation phenomenon on the Yoni Al-Mubarok Mosque architecturein Nganjuk, East Java. This study used a qualitative approach in its analysis. This mosque was one of the oldestmosques in Nganjuk, which had an interesting and unique history. This mosque was born as part of AfdeelingBerbek's existence under the rule of Sosrokusumo I, also known as Kanjeng Jimat. The mosque as a place ofworship for Muslims did not have standard rules in its architecture. Hence, the peculiarities of the mosque'sarchitectural form emerged according to the surrounding cultures. Therefore, it was not surprising that the YoniAl-Mubarok Mosque was closely related to Hindu and Chinese cultures. It caused the Al-Mubarok Mosque tohad different architectural characteristics from other mosques in the Nganjuk region.